Literatura w dwunastowiecznym Konstantynopolu - zmiana kierunków? - Jeffreys, Elisabeth (Przegląd Nauk Historycznych, 2009)
The author sketches the intellectual landscape of twelfth-century Constantinople with the special reference to the trends in literature and variety of its genres.The period, dominated by the Komnenos dynasty, with an increasing economic prosperity and all its cultural and social consequences, generated a demand for trained bureaucrats in secular and ecclesiastical spheres and, as far as writers and literary practitioners are concerned, provided new possibilities of imperial and aristocratic families' patronage. By the 1120s and 1130s a more regular provision of higher education was in existence in Constantinople to such an extent that supply had outstripped demand. It bore a great significance as the extent to which writers depended on the patronage as their sole means of support was a new feature of the era. John Tzetzes' career is quoted as an example of this process and his literary output, covering much that would be classed now not as a literature but e.g. scholarship, leads to a problem of an understanding of a literature itself.The characteristic features of byzantine literature of the period are named, f.ex. the linguistic usages in fine writing, that followed those of the ancient grammarians and dictionaries and only on very rare occasions using the vernacular language that was in current use. The Byzantine literary production of the time, understood widely, conforms on the whole to the pattern, in which a deeply Christianized society focuses its most attention on composing and preserving material produced as aids to correct Christian thought and worship. In a consequence, secular material formed a very small proportion of the total writerly output and the existing literary forms aspired to conveyed material abhorent to many of the literary practitioners.There are, on the other hand, three particularly important divergences from what could be perceived as the standard Byzantine pattern. Writing in vernacular, colloquial Greek appears quite suddenly, usually in snippets, breaking the linguistic self-censorship that had been in place for centuries. Erotic fiction, created by Theodore Prodromos, Constantine Manasses. Niketas Eugenianos. Eumathios Makrembolites and the anonymous author of Digenis Akritis, reappeared in the form of novels created under the profound influence of the late antique authors. The third aspect is the copious production of verse for special occasions, a long Byzantine habit, deriving from the epideictic oratory of the Second Sophistic, and in the twelfth century widespread in the imperial and aristocratic households. The last part of the lecture focuses on Manganeios Prodromos, an author whose poetry of this genre survived, as well as on his social and literary connections (including a role of sevastokratorissa Eirene and lakovos Monachos).